Meningkatkan Pemahaman Membaca Melalui Penggunaan Membaca Ekstensif dalam Pengajaran Siswa Sekolah Menengah Pertama - Ambarsari, Lies; Huzein, Tan (INTELEKTIUM, 2024)
This research was conducted to find out and investigate the student’ reading comprehension through the use of extensive reading in teaching at MTs. Fatahillah, South Jakarta. This research use qualitative research method which its approach is case study. The researcher use questionnaires and interview as the instruments of this research. Twenty four students as participants in this research. Based on the findings it is shown that participants feel anxious if they don't know all the words. They also feel anxious if they are not sure whether they understood what they read. Second, all of the participants agreed to think that reading is useful to shape personality. But they think they still cannot read quickly and their reading ability is still not advanced, even though half of them think they read a lot already. In conclusion, first teachers should give students friendly environment for students to read relax and comfort. Second, teachers need to influence the students’ habits and attitudes toward English reading by facilitating them interesting books such as comics and novels regularly. Third, parents or elder relative encourages students to engage in a large amount of reading books at home.